Potensi Metabolit Sekunder Asal Bakteri Endofit dalam Menekan Pertumbuhan Miselium Ganoderma boninense - Fitri Widiantini; Ceppy Nasahi; Endah Yulia; Serly Noviyawati (Jurnal Fitopatologi Indonesia, 2018)
Potency of Endophytic Bacterial Secondary Metabolite to Inhibit Mycelium Growth of Ganoderma boninense  Endophytic bacteria have a close relationship with their host plants. The bacteria are living inside their host without causing any symptom. Endophytic bacteria are well known for their ability to produce compounds that can be used to protect plants from deleterious microorganisms. The research was conducted to determine the ability of endophytic bacteria in producing antifungal compounds that are able to suppress the growth of Ganoderma boninense, a causal agent of basal stem rot disease of oil palm. Previously isolated endophytic bacteria were grown on international streptomyces project 2 (ISP2) liquid medium and incubated at rotary evaporator at 120 rpm for 10 days. The supernatant was separated from bacterial cells and tested against G. boninense using well diffusion agar method.  The results showed that endophytic bacteria isolate of BEK6, BEK7, BEK9 and BEK10 were able to produce antifungal compound against G. boninense. Microscopic observation demonstrated G. boninense mycelia alteration following secondary metabolite application.